Proterozoic Basic Magmatism of the Siberian Craton: Main Stages and Their Geodynamic Interpretation - Gladkochub, D.; Donskaya, T.; Ernst, R.; Mazukabzov, A.; Sklyarov, E.; Pisarevskiy, Sergei; Wingate, M.; Söderlund, U. (M A I K Nauka - Interperiodica, 2012)
Geological data on the Precambrian basic complexes of the Siberian Craton and their isotopic ageare considered. The three main episodes of Precambrian basic magmatism of Siberia correspond to certain stages of the geodynamic evolution of the craton and the Earth as a whole. In the Late Paleoproterozoic, largely in the south and the north of the craton, the basic rocks were emplaced against the background of post collision extension, which followed the preceding collision–accretion stage responsible for the formation of the craton. In the Mesoproterozoic, primarily in the north of the craton, basic magmatism was controlled by dispersed withinplate extension apparently caused by the impact of a mantle plume. Neoproterozoic basic magmatism widespread in the southern and southeastern parts of the craton was caused by rifting, which accompanied breakdown of the Rodinia supercontinent and opening of the Paleoasian ocean along the southern margin of the Siberian Craton.